Characterization of Crystalline CsPbBr3 Perovksite Dosimeters for Clinical Radiotherapy - Bruzzi, Mara; Talamonti, Cinzia (Frontiers in Physics, 2021)
Lead halide perovskite CsPbBr3 is a wide gap semiconductor material potentially very attractive for the next generations of real-time monitors. Here, we present the first characterization of crystalline CsPbBr point-dosimeters with sub-millimeter size, under 6MV X-photon beams used in clinical radiotherapy. The current response of the devices proved to be promising: the fast rise and decay times; absence of polarization effects; reproducibility to repeated irradiations; linearity of the collected charge as a function of the absorbed dose. Comparing the measured sensitivity with the theoretical one, a charge collection distance of about 200um has been evaluated, the same order of the linear dimensions of crystallites within the samples, suggesting that recombination centers are mainly placed at grain boundaries. A much higher sensitivity per unit area measured with crystalline CsPbBr3 as compared with drop-casted ones, can be explained in terms of a less disordered crystalline structure. This work opens the way to CsPbBr3 point dosimeters with linear dimensions meeting the strict spatial resolution constraints for bidimensional dose mapping required in clinical radiotherapy.